Relationship between Mycobacterium tuberculosis genotype and the clinical phenotype of pulmonary and meningeal tuberculosis - Simmons, Cameron (2018)
We used large sequence polymorphisms to determine the genotypes of 397 isolates of Mycobacterium tuberculosis from human immunodeficiency virus-uninfected Vietnamese adults with pulmonary (n = 235) or meningeal (n = 162) tuberculosis. We compared the pretreatment radiographic appearances of pulmonary tuberculosis and the presentation, response to treatment, and outcome of tuberculous meningitis between the genotypes. Multivariate analysis identified variables independently associated with genotype and outcome. A higher proportion of adults with pulmonary tuberculosis caused by the Euro-American genotype had consolidation on chest X-ray than was the case with disease caused by other genotypes (P = 0.006). Multivariate analysis revealed that meningitis caused by the East Asian/Beijing genotype was independently associated with a shorter duration of illness before presentation and fewer cerebrospinal fluid (CSF) leukocytes. Older age, fewer CSF leukocytes, and the presence of hemiplegia (but not strain lineage) were independently associated with death or severe disability, although the East Asian/Beijing genotype was strongly associated with drug-resistant tuberculosis. The genotype of M. tuberculosis influenced the presenting features of pulmonary and meningeal tuberculosis. The association between the East Asian/Beijing lineage and disease progression and CSF leukocyte count suggests the lineage may alter the presentation of meningitis by influencing the intracerebral inflammatory response. In addition, increased drug resistance among bacteria of the East Asian/Beijing lineage might influence the response to treatment. This study suggests the genetic diversity of M. tuberculosis has important clinical consequences.